The Impact of Domestic Financing for Investments on Economic Growth: An Applied Study Using Panel Data Analysis - Biltagy, Marwa; Fath-Allah, Mahmoud R.; Zoreik, Asmaa (International Journal of Economics and Financial Issues, 2025)
This study examines how reliance on domestic financing for investments, measured by the self-financing ratio (SFR), impacts economic growth. The research also examines how factors such as financial development, government budget balance, and income levels influence this relationship, using annual data from 83 countries (2005 to 2021). A system generalized method of moments (System GMM) is used to study the relationship between SFR and growth. The results show that income level affects the SFR-growth relationship. Specifically, the SFR positively and significantly impacts growth in high-income countries and the total sample. Furthermore, income level influences the relationship between economic growth and the interaction terms of the financial development index and government budget balance with the SFR. This study is considered the first to incorporate the IMF’s financial development index as an interaction term with SFR to examine how a country’s financial development influences the domestic financing for investments and economic growth relation.